2013
DOI: 10.1007/s10953-013-0099-2
|View full text |Cite
|
Sign up to set email alerts
|

Stabilities of the Divalent Metal Ion Complexes of a Short-Chain Polyphosphate Anion and Its Imino Derivative

Abstract: The stability constants of ML-type complexes of the two linear triphosphate ligand anion analogues triphosphate (\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$ {\text{P}}_{ 3} {\text{O}}_{10}^{5 - } $$\end{document}) and diimidotriphosphate (\documentclass[12pt]{minimal} \usepackage{amsm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…Figure S9d showed a higher amount of Cu 2+ /Zn 2+ /Mn 2+ uptake by δ-MnO 2 surface. Total P uptake by δ-MnO 2 in the presence of Cu 2+ , Zn 2+ , and Mn 2+ was also higher than that in the presence of Ca 2+ and Mg 2+ (Figure S9c), possibly due to the stronger affinity of Cu 2+ /Zn 2+ /Mn 2+ to phosphate groups and Mn oxide surface. , …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Figure S9d showed a higher amount of Cu 2+ /Zn 2+ /Mn 2+ uptake by δ-MnO 2 surface. Total P uptake by δ-MnO 2 in the presence of Cu 2+ , Zn 2+ , and Mn 2+ was also higher than that in the presence of Ca 2+ and Mg 2+ (Figure S9c), possibly due to the stronger affinity of Cu 2+ /Zn 2+ /Mn 2+ to phosphate groups and Mn oxide surface. , …”
Section: Resultsmentioning
confidence: 95%
“…Total P uptake by δ-MnO 2 in the presence of Cu 2+ , Zn 2+ , and Mn 2+ was also higher than that in the presence of Ca 2+ and Mg 2+ (Figure S9c), possibly due to the stronger affinity of Cu 2+ /Zn 2+ /Mn 2+ to phosphate groups and Mn oxide surface. 34,35 Hydrolysis of Ca-PolyP Solid Granules. The effect of polyP phase (solid vs dissolved) on its hydrolysis was also investigated in the presence of α-MnO 2 (Figure 7), as previous studies have suggested the abundant presence of scattered micron-sized Ca-polyP particles in marine sediments.…”
Section: Acs Earth and Space Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies on the acid dissociation, complex formation and pyrolysis behaviors of short-chain imidophosphates and cyclo-μ-imidotriphosphates as six-membered compounds. [36][37][38][39][40][41][42] On the other hand, except for cyclotetra-μ-imidotetraphosphate anions as shown in Fig. S1, † 43,44 all four bridging atoms of which are nitrogen atoms, neither synthesis nor isolation has been reported for a series of cycloμ-imidotetraphosphates as an eight-membered compound.…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47][48][49][50][51] Consequently, the cyclo-diμ-imidotriphosphate sodium salt, Na 3 cP 3 O 7 (NH) 2 , in which one of the bridging nitrogen atoms in cyclo-tri-μ-imidotriphosphate sodium salt, Na 3 cP 3 O 6 (NH) 3 , was replaced by an oxygen atom, is applied to a starting material for the synthesis of diimidotriphosphate sodium salt, Na 5 P 3 O 8 (NH) 2 , which has a short chain molecular structure. 37,38,52 Similarly, Na 4 cP 4 O 9 (NH) 3 is expected to be used as a starting material for the synthesis of Na 6 P 4 O 10 (NH) 3 . In this study, a novel method and pH-controlled recrystallization for the synthesis of Na 4 cP 4 O 9 (NH) 3 were developed, and the dependence of the protonation equilibria of various cyclo-μ-imidotetraphosphate anions, cP 4 O 12−n (NH) n 4− (n = 0, 2, 3, 4), on the number of imino groups which constitute the ligand molecules was investigated by potentiometric titrations and 31 P NMR measurements.…”
Section: Introductionmentioning
confidence: 99%